Active plasma sterilizer for planetary protection and contamination control for space missions - Subrata Roy; Justin Kosky; Tamara Revazishvili; Sarthak Roy; Sierra Brown; Vladimir Vichnyakov; Nona Rurua; Emma Noelle Mastro; Davit Kobaidze (Scientific Reports)
Abstract This paper introduces a novel, compact plasma sterilization system, the Active Plasma Sterilizer (APS), for planetary protection space missions. The development of the APS system is done through iterative testing and design modifications aimed at addressing decontamination modalities for time and temperature, cleaning adhesive surfaces, and cleaning protocols beyond alcohol and bleach. Decontamination testing of Deinococcus radiodurans, Geobacillus stearothermophilus (spore forming bacteria), and Aspergillus fumigatus (fungi) was verified for the APS on relevant materials of 4 to 5 log reduction up to complete killing in 45 min or less. The material compatibility testing of the APS performed with Stainless Steel 316, Teflon PTFE, and FR-4 PCB using a single exposure showed no visible material degradation through SEM analysis. This study demonstrates the efficacy of the APS technology for use with planetary protection due to its low-temperature operation, low weight and size, zero-plumbing requirements, safety features, decontamination capabilities, and material compatibility.